Molecular Recognition of Wax Inhibitor Through Pour Point Depressant Type Inhibitor - Norida, Ridzuan; Fatmawati, Adam (2014)
The deposition or crystallization of wax paraffin from crude oils is one of the crucial issues faced in the petroleum industry particularly when the temperature of the crude oil is below the wax appearance temperature (WAT). Pour point depressants (PPDs) chemical is proven to be an efficient way to solve this problem. This study investigated poly(ethylene-co-vinyl acetate(EVA)) and Poly(maleic anhydride-alt-1-octadecene)(MA) polymers inhibitors on the van der Waals intermolecular interaction between the major wax component molecule n-Octacosane C28H58, via molecular dynamics simulation (MD) technique on Material Studio 5.5 software Package. COMPASS force field was applied to analyse the desired structural property Radial Distribution Function (RDF). The results showed that the radial distribution function and g (r) value shows that is able to give the insight on which particular type of atoms were benefit to inhibit the self-agglomerate of the wax crystal formation. The present of carbonyl oxygen in EVA play a significant role to inhibit the wax formation through the van der Waals interaction between active hydrogen atoms in n-Octacosane molecule. Therefore the chances of wax inhibition in octacosane is less by introduce EVA as inhibitor compare to MA.